2019
DOI: 10.21037/atm.2019.12.23
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic hypomethylation and upregulation of GD3s in triple negative breast cancer

Abstract: Background: Breast cancer remains a major health problem in the world. Triple-negative breast cancer (TNBC) is an aggressive subtype with very poor prognosis. Up to now, the mechanism behind TNBC's activity is still unclear and no candidate drug target has been identified. Thus, it is of critical importance to elucidate the pathways in TNBC and identify the relevant biomarkers. Recent studies showed that ganglioside D3 synthase (GD3s) played a very important role in development of cancers. However, the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In this study, six hypo-methylated clusters for GAC were generated with different OS profiles, the patients’ OS and tumor progression become worse as the methylation level decreases, and MSI was inversely proportional to hypomethylation. Hypomethylation can promote the up-regulation of proto-oncogenes or tumor progression-related genes through various pathways, thereby changing the biological behavior of cancer 26 28 , which is consistent with our results. Currently, people are generally keen to study the phenomenon of hypermethylation in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, six hypo-methylated clusters for GAC were generated with different OS profiles, the patients’ OS and tumor progression become worse as the methylation level decreases, and MSI was inversely proportional to hypomethylation. Hypomethylation can promote the up-regulation of proto-oncogenes or tumor progression-related genes through various pathways, thereby changing the biological behavior of cancer 26 28 , which is consistent with our results. Currently, people are generally keen to study the phenomenon of hypermethylation in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…In metastatic melanoma high ST8Sia1 expression is associated with detrimental outcome and higher expression in metastatic lesions, particularly in the brain (201). Recent studies analyzing data from The Cancer Genome Atlas (TCGA) showed an association of high ST8Sia1 expression levels in breast cancer with poor patient survival (202)(203)(204), which is eventually linked to epigenetic hypomethylation of the ST8SIA1 gene (204). As opposed, in another study higher expression of ST8Sia1 mRNA in estrogen receptor (ER) positive breast cancer patients has been associated with higher disease free survival, while no significant difference was found in ER negative patients (205).…”
Section: St8sia1/gd3 Synthasementioning
confidence: 99%
“…FGFR aberrations were harbored by 6.2% (552/8,922) of the patients with lung cancer in our study, with the majority of aberrations occurring in FGFR1 (59.6%, 311/552), followed by FGFR3 (119/552) and FGFR2 (60/552). FGFR4 aberrations were detected in 16 Mutation refers to all non-amplification, non-fusion mutations including insertions or deletions, single base substitutions, multiplenucleotide substitutions, and copy number deletion. N, screened population; amp, amplification.…”
Section: Somatic Aberrations Of Fgfrs Across the 16 Cancer Typesmentioning
confidence: 99%
“…For instance, FGFR1 has been reported to be amplified in as many as 19% of squamous cell lung carcinomas (13), 6% of small cell lung carcinomas, and 1% of lung adenocarcinomas (14). FGFR1 amplification is also prevalent in breast cancer, with 15% of hormone receptor-positive breast cancers and 5% triple-negative breast cancers (TNBC) have been found to harbor FGFR1 amplification (15)(16)(17). FGFR2 amplification, which occurs less frequently than FGFR1 amplification, is present in 4-9% of gastric cancers, especially in diffuse-type gastric cancer (18), and is often associated with poor prognosis (19).…”
Section: Introductionmentioning
confidence: 99%